The effectiveness of lesson plan (RPP) in improving science generic skills through STEAM-based learning on human respiratory system material in junior high school - Rezky Nefianthi; Rabiatul Adawiyah; Syahbudin Syahbudin (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
The STEAM (Science, Technology, Engineering, Art and Mathematics) learning model that links the fields of science, technology, engineering, art, and mathematics, so that students are given a holistic understanding. Collaboration, cooperation and communication will appear in the learning process because this approach is carried out in groups. This study aims to determine the effectiveness of the Lesson Plan in improving STEAM-based Science generic skills in the Human Respiratory System material for Class VIII Junior High School. The development of this lesson plan refers to an educational problem solving model which consists of five phases or stages, namely the initial investigation phase, the design phase, the realization phase, the test phase, evaluation, and revision and implementation. Trial of lesson plan products that have been developed and declared valid was carried out in class VIII of SMP Negeri 24 Banjarmasin as many as 16 students. The instrument for collecting data on students' generic science skills was a written test. The results showed that the five aspects of Students' Science Generic Skills include formulating skills problems, formulating hypotheses, designing experiments, analyzing data and making conclusions always increases at each meeting and the value obtained is in the High category. This result is reinforced by the teacher's response with very good category.Abstrak Model pembelajaran STEAM (Sains, Technology, Engineering, Art and Mathematic) yang mengaitkan bidang ilmu pengetahuan (sains), teknologi, teknik, seni, dan matematika, sehingga siswa diberikan pemahaman holistik. Kolaborasi, kerja sama dan komunikasi akan muncul dalam proses pembelajaran karena pendekatan ini dilakukan secara berkelompok. Penelitian ini bertujuan untuk mengetahui efektifitas Rencana Pelaksanaan Pembelajaran (RPP) dalam meningkatkan keterampilan generik Sains berbasis STEAM pada materi Sistem Pernafasan Manusia Kelas VIII SMP. Pengembangan RPP ini mengacu pada model pemecahan masalah pendidikan yang terdiri dari lima fase atau tahapan, yaitu fase investigasi awal, fase desain, fase realisasi, fase tes, evaluasi, dan revisi serta implementasi. Uji coba produk RPP yang telah dikembangkan dan dinyatakan valid dilakukan di kelas VIII SMP Negeri 24 Banjarmasin sebanyak 16 orang siswa. Instrumen pengumpulan data keterampilan generik sains siswa dengan tes tertulis. Hasil penelitian menunjukkan bahwa lima aspek Keterampilan Generik Sains Siswa meliputi keterampilan merumuskan masalah, merumuskan hipotesis, merancang percobaan, menganalisis data dan membuat kesimpulan selalu meningkat pada setiap pertemuan dan nilai yang diperoleh kategori tinggi. Hasil ini diperkuat dengan respon guru dengan kategori sangat baik.